Simulation-dynamic model of influence of various advertisement on sales of services. (November 2020) - Tynchenko, V S; Kukartsev, V A; Yamshchikov, A S; Kukartsev, V V; Farafonov, M M
Abstract: The article considers the influence of various types of advertising and identifies those that have the greatest impact on sales of services of different organizations. The model is built with consideration of the following types of advertising: event advertising, advertising on social networks, television and outdoor advertising. Also taken into account communication that has the greatest influence on the increase in the purchase of services. The constructed model is aimed at modelling the acquisition of service once and does not consider modelling repeat purchases. Based on the constructed graphs, changes in the number of existing and potential customers and the effect on the flow of customers from various types of advertising are analyzed. From this, conclusions were drawn about which particular type of advertising has the greatest impact, and which is the least and how communication affects the acquisition of services.